Comparison of electrode diameter-based and heat input-based methods for estimating the number of weld passes in shielded metal arc welding (SMAW) - Susilo Handoko; Regan Rahadian Pambudi (Journal of Welding Technology, 2026)
Selecting the appropriate number of weld passes is an important step in Shielded Metal Arc Welding (SMAW) because it influences weld quality, heat input, productivity, and metallurgical characteristics of the welded joint. Existing approaches, such as the heat input-based procedure proposed by Trindade, provide reliable estimates by considering welding heat input and allowable thermal limits but require detailed welding parameters that are often unavailable during the initial stage of welding procedure planning or impractical to calculate on the production floor. This study proposes a simplified empirical equation for estimating the required number of SMAW weld passes using only plate thickness and the smallest electrode diameter. The proposed equation was evaluated by comparison with a modified heat input-based procedure derived from Trindade and integrated with EN 1011-2:2001 through Carbon Equivalent (CET) assessment. The comparison was conducted for single V-groove butt joints in the 1G position using a 2.6 mm E7016 electrode on plate thicknesses of 5, 8, 10, 12, and 16 mm. The proposed method predicted 2, 4, 4, 5, and 7 weld passes, whereas the modified heat input method required 2, 4, 6, 8, and 15 passes, respectively. Both methods produced identical results for plate thicknesses up to 8 mm; however, the discrepancy increased for thicker plates because the proposed equation does not account for groove geometry, welding travel speed, deposition rate, or heat input. The results demonstrate that the proposed equation provides a rapid and practical preliminary estimation tool for low-thickness SMAW joints, enabling fabrication personnel to estimate the required number of weld passes within seconds using only readily available parameters before detailed heat input verification is performed.